St Augustine's Confessiones : the role of the imago Dei in his conversion to Catholic Christianity - Roos, Andre (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Ancient Studies))--University of Stellenbosch, 2011.